Gender Equality and Coastal Climate Resilience: Women's Agency in Indonesia, Vietnam, and Bangladesh - Sus Eko Zuhri Ernada; Honest Dody Molasy; Robbyn Alders (Journal of Feminism and Gender Studies, 2026)
Coastal communities in Indonesia, Vietnam, and Bangladesh are increasingly exposed to climate-related hazards that threaten livelihoods, ecosystems, and social well-being. Although previous studies have extensively documented women's vulnerability to climate change, comparatively little attention has been paid to the mechanisms through which gender equality strengthens coastal climate resilience across different governance contexts. This study examines the relationship between gender equality and coastal climate resilience through a qualitative comparative analysis of Indonesia, Vietnam, and Bangladesh. The analysis integrates primary evidence from Focus Group Discussions (FGDs) conducted in Indonesia with secondary evidence from Vietnam and Bangladesh, complemented by policy documents and scholarly literature. Data were analysed using thematic analysis. The findings demonstrate that women make substantial contributions to climate adaptation through livelihood diversification, local ecological knowledge, environmental stewardship, collective action, and disaster preparedness. However, these contributions remain constrained by unequal access to productive resources, limited participation in decision-making, and persistent socio-cultural and institutional barriers. The comparative analysis further demonstrates that gender equality strengthens adaptive capacity by enabling women's agency, while inclusive governance determines the extent to which this agency can be translated into long-term coastal climate resilience. The study advances an integrated conceptual framework positioning women's agency as the central mechanism linking gender equality, adaptive capacity, and coastal climate resilience across diverse institutional contexts. These findings contribute to Feminist Political Ecology by demonstrating that resilient coastal communities are shaped not only by technological adaptation but also by inclusive governance that recognises women's knowledge, participation, and leadership.